The age of quality innovation - Sang M. Lee (International Journal of Quality Innovation, 2015)
In this inaugural issue of International Journal of Quality Innovation, the Editor-in-Chief reports the evolution of quality management and the need for innovative research for creating new quality values.
Keywords: 650; Evolution of quality concepts; Age of quality innovation; New quality values